Clinical severity of serum S100A12 levels in patients with osteoarthritis and S100A12 open inflammation of osteoarthritis model by NLRP3. (May 2021) - Li, Zhi; Zhai, Weitao; Sun, Qinggang; Hu, Shipeng; Ma, Yinghui; Zhang, Bin
Osteoarthritis is a common chronic bone and joint disease, which is characterized by degenerative changes and destruction of articular cartilage, secondary hyperostosis. This study aimed to investigate the clinical severity and mechanism of S100A12 in patients with osteoarthritis. Serum samples were obtained from patients with osteoarthritis or normal volunteer in Minhang Branch of Yueyang Hospital of Integrated Traditional Chinese and Western Medicine affiliated to Shanghai University of Traditional Chinese Medicine (Shanghai, China). C57BL/6J mice performed Resection of the medial collateral ligament and medial meniscus as mice model. MC3T3-E1 cells were induced with 100 ng of LPS as vitro model. The serum level of S100A12 was increased in patients with osteoarthritis. Similarly, S100A12 levels of serum and bone tissue from mice model of osteoarthritis were also higher than those of sham group. Over-expression of S100A12 promoted inflammation levels while down-regulation of S100A12 decreased inflammation levels in in vitro model of osteoarthritis. NLRP3 is an important target of S100A12 in pro-inflammation effects of osteoarthritis. NLRP3 was involved in the effects of S100A12 on inflammation in in vitro model of osteoarthritis. S100A12 also accelerated inflammation by NLRP3 in mice model of osteoarthritis. We conclude that serum S100A12 levels was a possible clinical severity, open inflammation of osteoarthritis model by NLRP3 and its receptors may be effective in preventing the development of osteoarthritis.